Microcontroller-based Design a Supporting System for Irradiance, Temperature and Tilt Angle Conditioning of PV Performance Measurement - Idris, Ahmad Rosyid; Usman, Usman; Fauzan, Faturahman; Achmad, Alamsyah (Jurnal Teknik Elektro, 2024)
Several factors influence PV output, including irradiance, temperature, and panel tilt angle. Irradiance and tilt angle affect the Photovoltaic (PV) current, while temperature affects the PV voltage. To accurately measure the performance of PVs in the field, it is necessary to condition these three parameters. Therefore, a system should be created to condition these parameters. This research aims to develop a control and monitoring system based on the set point to condition irradiance, temperature, and tilt angle. This research started with system design, fabrication, and functionality testing with the black box method, sensor reading accuracy, and PV performance testing. The functionality testing results indicate that each test item can perform as expected. The sensor testing revealed 1%, 0.26%, and 1.8% errors for MLX90614, BH1750, and MPU6050, respectively. The system's performance was tested, and it was discovered that the input value, which is the setpoint of the three variables, i.e., irradiance, temperature, and tilt angle of the PV, can produce outputs that are almost the same as the input value and settling time is different to reach the setpoint of each parameter. PV performance measurement using this system can represent PV performance by conducting direct testing using direct sunlight.